Study On Microbiological Profile of Endotracheal Secretionsin Patients on Mechanic Ventilators - Priyadarshi Sharma; Nidhi Sharma (Asian Journal of Medical Research, 2019)
Background: Respiratory infections in critically ill patients are associated with high morbidity and mortality. Rapid diagnosis and initiation of appropriate antibiotic therapy is essential for better outcomes. Patients who are intubated and mechanically ventilated are further at risk of acquiring respiratory infections due to complex interplay between the endotracheal tube, host immunity and virulence of invading bacteria, which may lead to Ventilator Associated Pneumonia (VAP). Subjects and Methods:307 total numbers of cases were included. Among all 209 cases did not develop respiratory infection & 98 cases developed respiratory infection. This study conducted in the Department of TB & Chest in Geetanjali Medical College, Udaipur, Rajasthan, India. The duration of study was over a period of six month. Results:In this study 307 total numbers of cases were included. Among all 209 cases did not develop respiratory infection & 98 cases developed respiratory infection. Out of 98 cases 47.9% were male & 52.1% were female who developed respiratory infection. In this study we suggested that 50% gram negative bacteria followed by 43.8% gram positive bacteria were found & 6.2% fungus isolate from the 98 cases.Conclusion: This study concludes that, Culture of ET aspirate is an easy, cost-effective procedure which helps in identifying the organism. If there are any delays in antibiotic treatment, it may lead to poor outcomes.